2014
DOI: 10.1097/mph.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastases, Skeletal-related Events, and Survival Among Children With Cancer in Denmark

Abstract: Bone metastases and skeletal-related events (SREs), including radiation therapy or surgery to bone, pathologic fracture, or spinal cord compression, among children have not been described in a population-based study. We examined the rate of bone metastasis, SREs, and survival in the Danish pediatric cancer population. We identified children below 18 years with a first-time diagnosis of cancer between January 1, 1994 and December 31, 2009 in the Danish Cancer Registry. From the Danish National Registry of Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Bone Scintigraphy is a famous method for imaging wide variations of benign or malignant skeletal abnormalities Although bone metastasis is uncommon among children with cancer [3], the main cause of referral was metastatic work up. This is attributed to the fact that skeletal-related events affects the disease future [3].…”
Section: Discussionmentioning
confidence: 99%
“…Bone Scintigraphy is a famous method for imaging wide variations of benign or malignant skeletal abnormalities Although bone metastasis is uncommon among children with cancer [3], the main cause of referral was metastatic work up. This is attributed to the fact that skeletal-related events affects the disease future [3].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed its elevated expression in various malignant tumors, including breast cancer and prostate cancer, and its correlation with patients’ prognosis, thereby suggesting its potential relationship with the invasion ability of the tumor [ 10 , 11 ]. DNA-microarray analysis found elevated expression of PMP22 in osteosarcoma tissues especially in those with high prevalence of metastasis [ 26 ]. These results suggest the potential oncogene role of PMP22 in the occurrence of osteosarcoma, but leaving its detailed mechanisms unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Bone metastases can occur in advanced neuroblastoma, osteosarcoma, or childhood sarcomas (such as Ewing sarcoma or rhabdomyosarcoma). 15 These sites cause somatic pain, though patients with extraosseous extension may experience paresthesias or neuropathic pain. Pain from bone metastases is a widely accepted indication for palliative RT.…”
Section: Bone Metastasesmentioning
confidence: 99%